2012
DOI: 10.1094/pdis-11-11-0957-re
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single and Double Infections of Winter Wheat by Triticum mosaic virus and Wheat streak mosaic virus on Yield Determinants

Abstract: Byamukama, E., Tatineni, S.. Hein, G. L., Graybosch, R. A., Baenziger, P. S., French, R., and Wegulo, S. N. 2012. Effects of single and double infections of winter wheat by Triticum mosaic virus and Wheat streak mosaic virus on yield determinants. Plant Dis. 96:859-864.Triticum mosaic virus (TriMV) is a recently discovered virus infecting wheat (Triticum aestivum) in the Great Plains region of the United States. It is transmitted by wheat curl mites (Aceria tosichella) which also transmit Wheat streak mosaic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Tatineni et al (26) demonstrated increased symptom severity and titer of each virus when winter wheat was co-infected with TriMV and WSMV. Similarly, Byamukama et al (2) and Wegulo et al (28) showed that, under greenhouse and field conditions, coinfection of a WSMV-susceptible winter wheat cultivar with TriMV and WSMV significantly reduced yield and yield determinants and components compared with single infections.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Tatineni et al (26) demonstrated increased symptom severity and titer of each virus when winter wheat was co-infected with TriMV and WSMV. Similarly, Byamukama et al (2) and Wegulo et al (28) showed that, under greenhouse and field conditions, coinfection of a WSMV-susceptible winter wheat cultivar with TriMV and WSMV significantly reduced yield and yield determinants and components compared with single infections.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies have shown that co-infection of wheat with WSMV and TriMV results in synergism that increases symptom severity, elevates titers of both viruses (26), and exacerbates biomass and yield loss (2,28). Therefore, knowing the extent of the distribution of TriMV and the frequency of its co-infection of wheat with WSMV or HPV will assist in estimating the potential risk TriMV poses to wheat production.…”
mentioning
confidence: 99%
“…Mace is resistant to WSMV at temperatures below 19°C [53]. Mace’s resistance to WSMV is conditioned by the Wsm -1 gene, which is also found to provide similar levels of resistance to TriMV [8], [52]. Wsm-1 was introduced to wheat from the related perennial grass Thinopyrum intermedium (Host) Barkworth & D.R.…”
Section: Introductionmentioning
confidence: 99%
“…Because the wheat curl mite transmits all of these viruses, they are often found together in mixed infections in the Þeld (Mahmood et al 1998, Seifers et al 2008. The extent of the interaction of the viruses is not known; however, it is clear that where one or more viruses are present, the resulting disease complex signiÞcantly impacts wheat (Tatineni et al 2010, Byamukama et al 2012.…”
mentioning
confidence: 99%